THE VUCA ERA CREATES COVID-19 PANDEMIC IN INDONESIA BEING COMPLICATED - Adnan, Ricardi S; Anam, Fadlan Khaerul; Radhiatmoko, Radhiatmoko (Universitas Padjadjaran, 2021)
This article aims to analyze the confusion of information, uncertainty in the situation, and human puzzlement have overshadowed the actions of Indonesian citizens throughout 2020 until the end of January 2021 in line with the pandemic outbreak which have not yet ended and still cannot be predicted when it will end. Volatility, uncertainty, problems of complexity and ambiguity of the choices are conditions that have been described by the VUCA concept. Covid-19, which has infected more than one million people in the country, has caused a lot of excitement in various domains: economic, political, social, cultural, and various other aspects of life. By conducting a literature review from March 2020 to January 2021 and analyzing secondary data from Twitter and distributing short questionnaires through Google Form on August 2020, as 969 respondents in Java, Bali, Sumatera, Kalimantan, Sulawesi, Nusa Tenggara dan Papua Islands the authors found that the VUCA era facilitates various complexities in dealing with the Covid-19 pandemic. The clumsy policies create uncertainty way in the process of social transformation towards society who cares about health protocols. Some of the solutions offered by Bennet and Lemoine (2014) or Aura Codreanu (2016) are still insufficient to manage the changes that occur towards a better life. This article contributes ideas related to social action about new social care, togetherness, and responsibility for realizing a new normal life.